THE RELATIONSHIP BETWEEN ECONOMIC DEVELOPMENT AND DEMOCRACY: LESSONS FOR TRANSITION COUNTRIES - Đorić, Žarko M (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2019)
The consideration of causative and consequential relations between the political and economic dimension of social life, that is, passing the boundary line between economy and politics, is the main goal of this paper. In this sense, in the coordinate system of economy-democracy, the task that seems appropriate is a reflection of the controversy that economists, politicians, philosophers and sociologists have long struggled with: whether economic development precedes the building of democracy or democratic institutions contribute to economic growth. The issue of the sequence makes the basis of this controversy. If it would be possible to establish a clear order in terms of cause and effect, social development would have a much clearer formula, and man's effort would have a far greater effect on the topology of modern society.
Keywords: SOCIALISM; politics; line; empirism; effort; economy; economics; economic development; development of democracy; democracy; controversy; consequentialism; boundaries